Group Based Algorithm to Manage Access Technique in the Vehicular Networking to Reduce Preamble ID Collision and Improve RACH allocation in ITS - Subramanian, Ramprasad; Barua, Shouman; Cong Lam, Sinh; Ghosal, Pantha; Sandrasegaran, Kumbesan (International journal of wireless & mobile networks, 2014)
Intelligent transportation system (ITS) is an application which provides intelligence to the transportation and traffic management systems. Although the word ITS applies to all systems in the transportation but as per the European union directive, it is the application of Information and communication technology in the field of transportation is defined as ITS. The communication technology has evolved greatly today from 2G/3G to long term evolution (LTE). In this paper, the authors focus on the LTE and its application in the ITS. Since LTE offers excellent QoS, wide area coverage and high availability, it is a preferred choice for vehicle to infrastructure service. In this paper, the authors have proposed a group based node selection algorithm to reduce the preamble ID collision otherwise this uncoordinated preamble ID transmission by vehicle node (VN) will eventually clog the network and there will be a massive congestion and re-transmissions attempts by VNs to obtain the random access channel.